Edukasi Pembuatan dan Penggunaan Ramuan Jamu Saintifik Untuk Penyakit Asam Urat di Garasi Dakwah Sleman Yogyakarta - Kiki Rizki Handayani; Fitri Yuliani (ABDIMAS Madani, 2024)
The high prevalence of hyperuricemia among the elderly. The problem faced by the community is a lack of understanding of how to make and use scientific herbal medicines correctly. This community service aims to increase public understanding regarding herbal medicine in treating hyperuricemia. The method used to determine the level of public understanding is to carry out a pretest and posttest on participants using a questionnaire consisting of 10 multiple choice questions related to hyperuricemiaand herbal medicine. This activity was held on January 20 2024, the location of the activity was at the Dakwah Garage on Jalan Damai Siduharjo Sleman Yogyakarta. The target of the activity is the Muslimah Garasi Dakwah Study Participants. The activity was attended by 50 elderly and pre-elderly participants. The range of participants pretest scores before education regarding hyperuricemia and scientific herbal medicine was 0 – 49.9 (92%), 50 – 59.9 (8%), 60 – 100 (0%). Based on the pretest results, the majority of participants had a very poor level of knowledge regarding hyperuricemia and scientific herbal medicine. The range of participants posttest scores after education regarding hyperuricemia and scientific herbal medicine was 0 – 49.9 (0%), 50 – 59.9 (4%), 60 – 69.9 (8%). 70 – 79.9 (16%), 80 – 100 (72%). Based on the posttest results, the majority of participants had a very good level of knowledge regarding hyperuricemia and scientific herbal medicine. Based on the results of the pretest and posttest, it can be concluded that public knowledge about scientific herbal medicine for hyperuricemia has increased